The Effects of Group Psychological Counseling Program Using Art Feeling to Restore Resilience Quotient of Violently Domestic Abused Women in Social Assistance Center of Kamphaeng Phet Province - Tuila, Sirintra; Suksawat, Jirasuk; Na Ranong, Laddawan (Ratchaphruek Journal, 2020)
The objectives of this research were to compare 1)restoration resilience quotient of violently domestic abuse women before and after, and 2) resilience quotient result after experiment between experiment group and control group which were taken care by multi vocational teams. Sample group was20 persons who were violently domestic abused women. The sample was devised into 2 groups by simple random sampling methods which were 10 persons in both groups. Experiment tools in this research were (1) Program of psychological counseling to restore resilience quotient, and (2) Testing package of restore resilience quotient, with reliable coefficient 0.88. Statistics employed for data analysis were mean, standard deviation, and Mann-Whitney U Test and Wilcox on Sign-Rang test. This research found that the restoration resilience quotient of experiment sample before and after group psychological counseling program are significant different at statistical level 0.05, and after experiment of the restoration resilience with group psychological counseling program is significant difference from those with control sample group using support program form multi vocation team at statistical level .05.